1995
DOI: 10.1017/s0954579400006805
|View full text |Cite
|
Sign up to set email alerts
|

The influence of deviant peers on the development of boys' disruptive and delinquent behavior: A temporal analysis

Abstract: The concurrent and predictive influence of deviant peers on boys' disruptive and delinquent behavior was examined in a community sample of fourth- and seventh-grade boys, who were followed-up over six data waves. Analyses were conducted separately for three different types of behavior problems: authority conflict, covert, and overt disruptive behavior. Consistent with the existing literature, concurrent relations between peers' and boys' disruptive behavior were expected to be significant. A more informative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
120
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(132 citation statements)
references
References 19 publications
11
120
0
1
Order By: Relevance
“…Compared to the large number of studies exploring the moderating effect of family variables on the relationship between deviant peer association and delinquency (e.g., Coombs, Paulson, & Richardson, 1991;Farrell, Henry, Mays, & Schoeny, 2011;Galambos, Barker, & Almeida, 2003;Keenan et al, 1995;Lansford et al, 2003;Mason, Cauce, Gonzales, & Hiraga, 1994;Mrug & Windle, 2009;Poole & Regoli, 1979;Trucco, Colder, & Wieczorek, 2011;Vitario, Brendgen, & Tremblay, 2000;Warr, 1993;Zimmerman, Steinman, & Rowe, 1998), few have studied the moderating role of family functioning. Family functioning can be defined as "the quality of family life at the systemic level, such as wellness, competence, strengths, and weaknesses of a family" (Shek, 2005: p. 518).To the knowledge of the investigators, only one study conducted by Henry, Tolan, and Gorman-Smith (2001) adopted a composite score of family relationship (i.e., cohesion, communication, belief about family, shared deviant beliefs, support, and organization) and parenting practices (i.e., positive parenting, discipline effectiveness, discipline avoidance, monitoring/involvement) to investigate four possible models about the relationships among family functioning, peers and delinquency among 246 male adolescents.…”
Section: Family Functioning Deviant Peer Association and Delinquent mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the large number of studies exploring the moderating effect of family variables on the relationship between deviant peer association and delinquency (e.g., Coombs, Paulson, & Richardson, 1991;Farrell, Henry, Mays, & Schoeny, 2011;Galambos, Barker, & Almeida, 2003;Keenan et al, 1995;Lansford et al, 2003;Mason, Cauce, Gonzales, & Hiraga, 1994;Mrug & Windle, 2009;Poole & Regoli, 1979;Trucco, Colder, & Wieczorek, 2011;Vitario, Brendgen, & Tremblay, 2000;Warr, 1993;Zimmerman, Steinman, & Rowe, 1998), few have studied the moderating role of family functioning. Family functioning can be defined as "the quality of family life at the systemic level, such as wellness, competence, strengths, and weaknesses of a family" (Shek, 2005: p. 518).To the knowledge of the investigators, only one study conducted by Henry, Tolan, and Gorman-Smith (2001) adopted a composite score of family relationship (i.e., cohesion, communication, belief about family, shared deviant beliefs, support, and organization) and parenting practices (i.e., positive parenting, discipline effectiveness, discipline avoidance, monitoring/involvement) to investigate four possible models about the relationships among family functioning, peers and delinquency among 246 male adolescents.…”
Section: Family Functioning Deviant Peer Association and Delinquent mentioning
confidence: 99%
“…Several researchers have explored the moderating effect of family variables on the relationship between deviant peer association and delinquency, and have made mixed results (e.g., Coombs, Paulson, & Richardson, 1991;Farrell, Henry, Mays, & Schoeny, 2011;Galambos, Barker, & Almeida, 2003;Keenan et al, 1995;Lansford et al, 2003;Mason, Cauce, Gonzales, & Hiraga, 1994;Mrug & Windle, 2009;Poole & Regoli, 1979;Trucco, Colder, & Wieczorek, 2011;Vitario, Brendgen, & Tremblay, 2000;Warr, 1993;Zimmerman, Steinman, & Rowe, 1998). It remains unclear whether the buffering effect of family functioning exists or not, as few studies have examined family at a systemic level.…”
Section: Introductionmentioning
confidence: 99%
“…Affiliation with deviant peers has been identified as a proximal risk factor for youth delinquency (Keenan, Loeber, Zhang, Stouthamer-Loeber, & van Kammen, 1995). Because deviant peer affiliation may increase the likelihood that children are in dangerous environments, deviant peer affiliation also may be a risk factor for community violence exposure.…”
Section: Moderating Effects Of Peers and Familymentioning
confidence: 99%
“…Adolescents who associate with deviant peers have a substantially increased risk for adolescent problem behaviors. Keenan, Loeber, Zhang, Stouthamer-Loeber, and Van Kammen (1995) found that, in comparison to boys who did not have best friends who were truant or disobedient, disruptive boys who did have deviant peer associations had three to four times the odds of participating in covert and overt delinquent acts. Adolescents appear to reinforce each other's antisocial beliefs within deviant peer groups (e.g., Dishion, Patterson, & Griesler, 1994).…”
Section: Middle School and High School Yearsmentioning
confidence: 96%